Becoming a Christian Sexuality Educator - Ott, Kate M. (Religious education, 2021)
Holistic sexuality education is needed in churches and seminaries to promote sexual inclusion and flourishing as well as combat sexual violence and trauma. The scholarly and pedagogical resources exist to do this work; we need an ethical commitment to integrate them across the curriculum.